Peranan Akal Terhadap Iman (Suatu kajian analisis terhadap pemikiran HAMKA) - Mursalin Ilyas; Abdul Ghany (Jurnal Ilmiah Islamic Resources, 2021)
This research is a literature study that the author uses, so that it can be seen that reason and faith as two fundamental things in humans affect what they believe and do in their life movements. Intellect provides information to faith about the truth that exists, as well as information about something that has been believed.